EVALUASI KEBIJAKAN PEMERINTAH KOTA SEMARANG TENTANG BADAN PROMOSI PARIWISATA KOTA SEMARANG - Iqtyar, Odiakta; Santoso, R Slamet (Journal of Public Policy and Management Review, 2021)
Tourism in Semarang City has enormous potential, but in its implementation it is still inferior to other big cities, this is due to the lack of tourism promotion carried out. To assist and develop Semarang tourism, the Semarang City Government has formed the Semarang City Tourism Promotion Board (BP2KS) which is regulated in Semarang City Mayor Regulation Number 2 of 2012 concerning the Semarang City Tourism Promotion Board. This study attempts to evaluate the Semarang City Government Policy regarding the Semarang City Tourism Promotion Board regarding whether or not BP2KS should be formed. This research uses a qualitative approach and descriptive methods. This study uses evaluation indicators according to William Dunn based on Semarang Mayor Regulation Number 2 of 2012 concerning the Semarang City Tourism Promotion Board. The results of this study indicate that although BP2KS plays an important role in marketing and tourism development, the organization itself is still not optimal. BP2KS as an independent body still has many shortcomings such as a lack of clarity on the role of the organization, and the fulfillment of organizational tasks and functions that are still not optimal. Suggestions given to optimize BP2KS are making BP2KS infrastructure facilities so that the management and members of BP2KS can focus optimally on improving the tourism image of Semarang City, as well as implementing sustainable programs involving all elements, especially tourism industry players and the general public.